The Effect Of The Korean Wave On Nation Brand South Korea (Study On USU Physics Students) - Deninta Novienthia (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2022)
Global economic crisis that hit the world economy, demands countries to improve its market strategy. A country needs to manage its country image as a company managed its brand image. Because a powerful nation brand, will bring a great inbound and outbound effect as well. Inbound effect is related to investment and tourism, whereas outbound effect is related to export and human resources. Korea is one of those countries that are serious about building its Nation brand through the spread of its pop culture (Korean Wave) and spends million annually to the Korean Wave. It suggests a real discussion about the influence of the Korean Wave towards the Nation brand of South Korea.The aims of this research to determine the influence of the Korean Wave among the students of the Faculty of Social and Political Science, University of North Sumatra towards the Nation brand of South Korea.This research is an associate research with quantitative approach, carried out at the Faculty of Social and Political Science, University of North Sumatra from December 2016 to January 2017. Data collection was done by spreading the questionnaire to 148 respondents who knew and or like Korean pop culture, in this case, its music and drama.The research result shows that the Korean Wave has significant influence towards the Nation brand of South Korea. The amount of influence is equal to 48.6%, while the remaining 51.4% is influenced by other factors which were not examined in this study.